Teachers Assistant: a Web-based application using Java Server Pages and Java database connectivity - Barua, S. (Smc 2000 conference proceedings. 2000 ieee international conference on systems, man and cybernetics. 'cybernetics evolving to systems, humans, organizations, and their complex interactions' (cat. no.0, 2000)
The paper discusses a Web-based application that serves as a leading resource for linking educators to the community. This Web site provides individual teachers and school organizations a simple and effective means to communicate school/course-related information to the education community and also provides a means for interested parties to interact with the classroom and give feedback to the instructor online. The paper shows the feasibility of developing Web-based applications using several new application tools from the Java 2 Enterprise Edition and demonstrates some of the features of this new technology.